Norms and military interventions, guest post by Jacob I. Ricks - RICKS, Jacob (Institutional Knowledge at Singapore Management University, 2015)
On 10 February 2015, Prime Minister Prayuth Chan-ocha, with his usual candor, told reporters that “Thailand is different from other countries. If something cannot be solved [by the government], the military will solve it.”[1] This statement embodies a number of assumptions, but perhaps most important for Thailand today is the idea that military intervention is a perfectly legitimate method of overcoming political challenges.